Model Pembelajaran Contextual Teaching and Learning (CTL) dalam Pembelajaran Bahasa Arab - Depi Kurniati; Nopiyanti Nopiyanti; Zakiyah Arifa (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2021)
This study intended to determine the feasibility of the Contextual Teaching Learning model in Arabic learning at MTsN Batu. This research-based on the stigma that developed in society showed that learning Arabic was considered problematic and complicated. That caused the problems that came from teachers were the lack of professionalism in teaching and the limitations of the components that will affect the Arabic learning process's implementation in terms of learning models. While the problems that arose from students in learning Arabic were the necessary experience, school background, mastery of mufradat (vocabulary), and family environmental factors, which then impact difficulties in understanding reading and not being able to master Arabic in full either in grammar and its communication. This research used quantitative and qualitative method with a descriptive-analytical type. The participants in this study were 32 students at MTsN Batu East Java. Research data collected from the questioner, observation, interviews and documentation. The study's findings showed that the percentage of the feasibility of the Contextual Teaching Learning (CTL) learning model in Arabic learning was 82.44% with mean 140,16. This finding means that the Contextual Teaching Learning (CTL) learning model's implementation at MTsN Batu was in an outstanding category. The components of the Contextual Teaching Learning (CTL) learning model during the learning process have been fulfilled. This study indicated that the Contextual Teaching Learning (CTL) model during the Arabic learning process was suitable only for specific materials.